Estetyka technociał - Gajewska, Grażyna (Studia Europaea Gnesnensia, 2012)
The article deals with the cultural and contextual complexity of the modern and postmodern figure of the cyborg, or rather the human relation to technology. The main problem is the formulation of the scope of the aesthetics of techno-bodies or aesthetic of artificial bodies. it is a contribution to a more extensive problem concerning the aesthetics, condition and possibilities of development of contemporary human who enters more and more intensively and further and further into the postbiological era.